2011
DOI: 10.1093/hmg/ddr344
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive disruptions of the nuclear envelope invoke temporary loss of cellular compartmentalization in laminopathies

Abstract: The nuclear lamina provides structural support to the nucleus and has a central role in nuclear organization and gene regulation. Defects in its constituents, the lamins, lead to a class of genetic diseases collectively referred to as laminopathies. Using live cell imaging, we observed the occurrence of intermittent, non-lethal ruptures of the nuclear envelope in dermal fibroblast cultures of patients with different mutations of lamin A/C. These ruptures, which were absent in normal fibroblasts, could be mimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
305
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(324 citation statements)
references
References 51 publications
16
305
2
1
Order By: Relevance
“…Indeed, it has been reported that a disruption in the integrity of the nuclear membrane allows the passage of components and even organelles from the cytoplasm to the nucleus. 51 Consequently, the presence of mitochondria in the nucleoplasm should increase nuclear ROS to a level that can damage DNA.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Indeed, it has been reported that a disruption in the integrity of the nuclear membrane allows the passage of components and even organelles from the cytoplasm to the nucleus. 51 Consequently, the presence of mitochondria in the nucleoplasm should increase nuclear ROS to a level that can damage DNA.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…[6][7][8][9][10][11] NE ruptures can also be detected by monitoring fluorescent proteins tagged with a nuclear export signal (NES), which only enter the nucleus during NE rupture and are exported back into the cytoplasm once NE integrity is restored. 6,10 In addition to these fluorescent reporters, evidence of NE rupture comes from mitochondria and ribosomes that become mislocalized to the nucleus, and promyelocytic leukemia (PML) nuclear bodies found in the cytoplasm of cells that exhibited NE rupture. 6,7 In cells cultured on rigid substrates, spontaneous NE rupture is observed in circa 5% of cells over a 24 h period.…”
Section: Introductionmentioning
confidence: 99%
“…6,10 In addition to these fluorescent reporters, evidence of NE rupture comes from mitochondria and ribosomes that become mislocalized to the nucleus, and promyelocytic leukemia (PML) nuclear bodies found in the cytoplasm of cells that exhibited NE rupture. 6,7 In cells cultured on rigid substrates, spontaneous NE rupture is observed in circa 5% of cells over a 24 h period. 6,7,9 Depletion of lamins or expression of disease-causing lamin mutants that impair nuclear lamina stability increases NE rupture rates.…”
Section: Introductionmentioning
confidence: 99%
“…24 In multicellular eukaryotes, massive membrane remodeling occurs during mitotic NE-disassembly and post-mitotic NE reformation; we wonder how ESCRT-III will function in these contexts. Moreover, the capacity of ESCRT-III to repair plasma membrane wounds 15,16 raises the possibility that it might also be capable of repairing the transient NE-ruptures that have been observed in several cancer cell lines 56,57 and in cells containing laminopathy mutations, 58 a model consistent with the growing role of ESCRT-III in membrane homeostasis and quality control.…”
Section: Discussionmentioning
confidence: 76%